Imagery Training’s Effect on the Level of Confidence of Futsal Athletes - Indrayogi, Indrayogi; Raharja, Didik Subhakti Prawira; Nurhayati, Maya (Jurnal Kepelatihan Olahraga, 2025)
Self-confidence is a psychological factor that plays an important role in athlete performance, including in the sport of futsal. One method that can be used to increase athlete confidence is imagery training, which is a mental visualization technique that involves certain images or scenarios to increase psychological readiness. This study aims to analyze the effect of imagery training on the level of self-confidence of futsal athletes. The method used in this study was an experiment with a pre-test and post-test design on a group of futsal athletes who were given imagery training interventions. Measurement of self-confidence is done using a self-confidence scale before and after the intervention. The instrument used in this study was a self-confidence questionnaire consisting of 13 questions. Data analysis was carried out using the t-test with a significance level of 5%. The results showed a significant effect of imagery training on the level of self-confidence of futsal athletes. This can be seen from the t value of 15.069, which is greater than the t table 1.729, as well as a significance value of 0.001, which is smaller than 0.005, with a percentage increase of 13.46%. The results showed that there was a significant increase in the level of confidence of athletes after participating in imagery training. This indicates that imagery can be an effective method in improving the psychological aspects of athletes, especially in increasing self-confidence when competing. Thus, imagery training is recommended as part of the training program for futsal athletes to support their optimal performance on the field.